ANALISIS STRUKTUR SISTEM PELAYANAN DAN TINGKAT KEDATANGAN SERTA KARAKTER ANTRIAN PADA SPBU PANGKALAN BALAI - FIRMANSYAH (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
The subject matter of this discussion is the analysis of the structure of the service system and the level of arrival and the character of the queues at the Pangkalan Balai SPBU. The objectives to be achieved from the results of this study were to determine the structure of the service system and the arrival rate and character of the queues at Pangkalan Balai SPBU.The method of analysis used in this research is this research uses qualitative methods, namely analyzing and observing existing data and adjusting it to the theories and then concludingThe results showed as follows: (1) The structure of the gas station service system is that customers enter the service area, then form a queue at each existing facility. Customers wait until it is time to get service at the facility, this stage is the time that is calculated as the waiting time in the system after the transaction process is complete, the customer leaves the area, the time required for each facility to provide different forms of service for each system, because customer needs are different at the same time, this is what can cause queues. The base station gas station operates 24 hours every day with the division of shifts into 3, namely the morning shift from 06.30-14.30 WIB, afternoon shift at 14.30-21.30 WIB and night shift at 21.30-06.30 WIB. During the break, the pangkalan balai gas station remains open, because the existing facilities take turns serving customers until the sales break, so that when the break time has finished all the facilities return to carry out their duties so that at break time the customers meet their needs. (2) The highest level of customers was at 12.00-18.00 hours with an average number of 284 motorbikes, while the lowest level of arrival was at 18.00-00.00 hours with an average number of 143 motorbikes. (3) The characteristics of the queuing system at the base station of the hall are as follows (a) Unlimited population, (b) Queuing discipline, (c) Arrival pattern, (d) Unlimited queue length.